The significance of the elections in Pakistan - Karzai, Hekmat (2009)
The global air power industry has gone through a tumultuous phase since the end of the Cold War. The industry is however now recovering, with implications for the industry in the Asia Pacific region. Smaller and emerging players have to adapt to survive.